Pemodelan Unified Model Languange Sistem Informasi Geografis Penentuan Lokasi Tempat Pembuangan Sampah Legal - Mardhiah Fadhli; Afifah Syahirah (Jurnal Informatika Universitas Pamulang, 2022)
In the development of an information system, a design or analysis stage is needed to identify system requirements to suit user needs. One of the design approaches in software development methodology is to use Unified Model Language (UML) modeling. UML modeling is a visual system design model that uses an object-oriented approach to make it easier for developers to design the system to be created. The analysis stage is the initial stage in identifying and designing the software requirements to be built. Making geographic information systems requires a reference in the design process so that it is easily translated by programmers in application development. One application of geographic information systems in the environmental field is mapping the distribution of legal waste disposal sites (TPS) in Pekanbaru City. Determination of legal TPS in the city of Pekanbaru is carried out by conducting surveys and measuring the area directly to the field. This of course takes time for officers to be able to recommend the area as a place to be used as a new TPS. The lack of information regarding the mapping of legal polling stations has also led to the emergence of illegal polling stations that can damage the environment. So it is necessary to build a geographic information system that can assist the Pekanbaru City Environment and Hygiene Service (DLHK) in determining recommendations for legal TPS-TPS locations based on spatial analysis and displaying a map of the distribution of existing TPS-TPS locations in Pekanbaru City. The development of this geographic information system was built with an object-oriented approach, so that in the process of analysis and design it uses UML Diagrams. UML diagrams made in this study are in the form of Use Case Diagrams, Usecase Descriptions, Activity Diagrams and Class Diagrams. The result of the research is that all the functionality designed in the use case diagram has been implemented in the application program 100%.